Valuation of Neutrophil/Lymphocyte Ratio in Renal Cell Carcinoma Grading and Progression - AKDENİZ, ESRA (CUREUS INC, 2018)
Introduction We investigated the association of the neutrophil/lymphocyte ratio (NLR) with tumor size and Fuhrman grade in nonmetastatic renal cell carcinoma (RCC) cases. Materials and methods Data of nonmetastatic RCC (T1-4N0M0) cases, operated between 2010 and 2016, were retrospectively reviewed and 103 patients were included in the study. The patients were divided into two groups according to tumor diameter (Group 1 T < 4 cm, Group 2 T >= 4 cm) and into three groups according to Fuhrman grade. Twenty-eight patients with a tumor diameter of 4 cm or less in Group 1 and 75 patients with a tumor diameter greater than 4 cm in Group 2 were compared. In both grouping systems, the NLR, mean platelet volume (MPV), red cell distribution width (RDW), white blood cell (WBC), red blood cell (RBC), platelet (PLT), lymphocyte, and neutrophil values and age were compared. Results There were no differences in age, MPV, RDW, neutrophil, WBC, RBC, PLT counts in groups of tumor diameter (Group 1 T < 4 cm, Group 2 T >= 4 cm). However, the lymphocyte amount was significantly higher in cases with a tumor diameter less than 4 cm compared to the cases with a tumor diameter greater than 4 cm (p = 0.015). It was observed that the NLR had a tendency to increase in patients with tumor size greater than 4 cm compared to patients with tumor size smaller than 4 cm (p = 0.029). There were no differences in age, MPV, RDW, lymphocyte, neutrophil, WBC, RBC, PLT counts, and the NLR in different Fuhrman-graded cases. Conclusions There is a linear relation between the tumor size and the NLR in nonmetastatic RCC cases. Therefore, the NLR is a cheap parameter that can be used to show the tumor size, and thus it can be used to get an idea about the prognosis of the patient.
Keywords: neutrophil/lymphocyte ratio; renal cell carcinoma; size; prognosis; TO-LYMPHOCYTE RATIO; C-REACTIVE PROTEIN; LATE RECURRENCE; NEUTROPHIL; SURVIVAL